2019
DOI: 10.1111/hex.12932
|View full text |Cite
|
Sign up to set email alerts
|

PERSPECTIVES: Stroke survivors' views on the design of an early‐phase cell therapy trial for patients with chronic ischaemic stroke

Abstract: BackgroundStem cell research holds the potential for a paradigm shift in the management of diseases such as stroke. Patient and public involvement in research (PPIR) can bring a focus to issues of clinical relevance and accelerate translation to real‐world clinical practice.ObjectiveA qualitative thematic analysis of the perspectives of stroke survivors regarding the conduct and design aspects of a proposed phase I clinical cell therapy study in stroke.DesignTwelve stroke survivors were purposively recruited i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
19
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(19 citation statements)
references
References 31 publications
(64 reference statements)
0
19
0
Order By: Relevance
“…Studies have reported a general positive attitude towards participation in cell therapy research, although with a wide divergence in efficacy expectations between study participants and research teams [ 39 ]. Our study revealed that patients had a pragmatic realistic approach to anticipated benefits [ 18 ]. It was interesting to note that patients were more worried about a loss of function as a possible risk as compared to more widely discussed risks such as tumorigenicity and death [ 18 ].…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…Studies have reported a general positive attitude towards participation in cell therapy research, although with a wide divergence in efficacy expectations between study participants and research teams [ 39 ]. Our study revealed that patients had a pragmatic realistic approach to anticipated benefits [ 18 ]. It was interesting to note that patients were more worried about a loss of function as a possible risk as compared to more widely discussed risks such as tumorigenicity and death [ 18 ].…”
Section: Resultsmentioning
confidence: 99%
“…Our study revealed that patients had a pragmatic realistic approach to anticipated benefits [ 18 ]. It was interesting to note that patients were more worried about a loss of function as a possible risk as compared to more widely discussed risks such as tumorigenicity and death [ 18 ]. The importance of measuring changes in often neglected outcomes such as cognition, mood, and overall ability to restore “normal” pre-stroke participation levels is a key insight that should inform future trial designs [ 18 ].…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Due to the small‐sized patient population and limited validated outcome measures, large randomized controlled trials (RCT) to establish whether an intervention is effective in rare diseases like haemophilia are often difficult to conduct without establishing whether a study is feasible 5,6 . In addition, resource use may not be optimally rationalized when a treatment or intervention is found to be ineffective or unsafe, or conversely, a treatment or intervention is not provided if it turns out to be effective 57 …”
Section: Introductionmentioning
confidence: 99%